Vlastivědný atlas České republiky - Břichňáčová, Eliška (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Diplomová práce se zabývá návrhem koncepce vyhotovení vlastivědného atlasu České republiky. Atlas má být určen pro žáky 1. - 2. ročníku základních škol a sloužit při výuce v hodinách prvouky. Pomocí této školní pomůcky by žáci měli získat základní znalosti o České republice a její návaznosti na Evropu a svět. První část diplomové práce se zabývá teoretickým postupem tvorby kartografického díla. Část druhá popisuje jeho praktické vyhotovení. Na závěr byla ověřena funkčnost atlasu mezi dětmi na Základní škole v Běrunicích.

Diploma thesis deals with proposal conception prepare homeland book of maps Czech republic. Book of maps will determined for pupils 1. – 2. class primary school and serve at teaching hours of elementary technig. Pupils should get basic information about Czech republic and her continuity on Europe and world with this school tool. The first part of the thesis deals with the theoretical process of cartographic work. Part two describes the her practical execution. At the end of atlas functionality was verified among children at an primary school in Běrunice.
Atlas of the Czech Republic for primary school
Keywords: Vlastivěda; atlas; Česká republika; Homeland; atlas; Czech republic